Over 780,000 farm households in South-East and East Asia adopt improved rice management practices - CGIAR Research Program on Rice (2021)
>780,000 farmers reached by the CORIGAP (Closing Rice yield Gap) project in South-East and East Asia, and the target yield increase was typically greater than 10%, and more importantly, the mean increase in income ranged from 15 to 90% because of increased yield and reduced input costs.